The Development of Module of Plant Species Resources in Kreo Cave Area of Semarang as a Source of Biodiversity Learning Materials in High Schools - Prayogo, Gogo; Rahayuningsih, Margareta; Rahayu, Enni Suwarsi (Journal of Innovative Science Education)
The purpose of this study is to analyze the plants species resources and the validity of Module according to the material experts, media experts, and teacher experts, to analyze the practicality, as well as the effectiveness of learning outcomes. This research used the R&D method. This research was conducted using the ADDIE method which was conducted at Islamic High School of Baitussalam involving 2 classes with 62 students in total. Descriptive data analysis was used. The results of the research on biodiversity in the Kreo Cave area which included the levels of genes, species, and ecosystems, found the results of each of the three levels of biodiversity totaling 24 types of plants which are the gene level 2 species, at the species level 7 species and at the ecosystem level at 15 species. The Module of plant species resources in the Kreo Cave area is theoretically feasible by means of validation sheets for material experts, media experts, and teacher experts with respective scores of 76%, 80%, and 81%, or are in the valid category. Student responses to the Module as a learning resource indicate that the Module is very valid. This is proven from the results of small-scale trials that reach an average value of 72% or are in good criteria. Student learning outcomes assessed during the learning process using Modules showed very good results. This is proven by the increase in students' cognitive from an average of 44.18 to 79.6..